2012
DOI: 10.1175/bams-d-11-00010.1
|View full text |Cite
|
Sign up to set email alerts
|

The Second Verification of the Origins of Rotation in Tornadoes Experiment: VORTEX2

Abstract: The second Verification of the Origins of Rotation in Tornadoes Experiment (VORTEX2), which had its field phases in May and June of 2009 and 2010, was designed to explore i) the physical processes of tornadogenesis, maintenance, and demise; ii) the relationships among tornadoes, tornadic storms, and the larger-scale environment; iii) numerical weather prediction and forecasting of supercell thunderstorms and tornadoes; and iv) the wind field near the ground in tornadoes. VORTEX2 is by far the largest and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 96 publications
4
92
0
2
Order By: Relevance
“…Over the last two decades, the international community has met this challenge through the use of mobile instrumentation, in particular the use of mobile weather radar (e.g., Wurman et al 2012;Weckwerth et al 2004). In an Australian first, a mobile pulsed Doppler lidar was deployed for the 2013/14 field campaign and a mobile polarimetric X-band radar (UQ-XPOL) was operated for the 2014/15 campaign (Fig.…”
Section: Experiments Motivation and Strat-egymentioning
confidence: 99%
“…Over the last two decades, the international community has met this challenge through the use of mobile instrumentation, in particular the use of mobile weather radar (e.g., Wurman et al 2012;Weckwerth et al 2004). In an Australian first, a mobile pulsed Doppler lidar was deployed for the 2013/14 field campaign and a mobile polarimetric X-band radar (UQ-XPOL) was operated for the 2014/15 campaign (Fig.…”
Section: Experiments Motivation and Strat-egymentioning
confidence: 99%
“…On 10 June 2010, during the second Verification of the Origins of Rotation in Tornadoes Experiment (VORTEX2; Wurman et al 2012), the NOAA X-Pol (NOXP) Doppler radar, SMART-R 2 (SR2) Doppler radar (Bigggerstaff et al 2005), StickNet , mobile mesonet surface observing platforms, and the Tempest unmanned aircraft system (UAS; Elston et al 2011) observed a RFGF, rear-flank outflow (RFO), and rear-flank internal surge of a supercell thunderstorm during its post-tornadic stage. This data set is unique in large measure because surface observations of these features were accompanied by UAS observations.…”
Section: Introductionmentioning
confidence: 99%
“…The structures and generation mechanisms of tornadoes have been studied by various methods such as theoretical study, laboratory experiment, numerical experiment, and field observation (recent reviews of the above subjects can be found in Wurman et al, 2012;Bluestein, 2013;Rotunno, 2013;Davies-Jones, 2014). Surface roughness is one factor that has significant impact on the flow structure and intensity of a tornado, which has been investigated by these means (e.g., Church and Snow, 1993;Natarajan and Hangan, 2012).…”
Section: Introductionmentioning
confidence: 99%